Escherichia coli O157:H7 and Salmonella species Isolated from Ducks and Indigenous chickens in live-bird Markets in Ibadan, Oyo State, Nigeria - Kolapo, Adedamilola; Amosun, Elizabeth; Olatoye, Olufemi; Adeoye, Fiyinfoluwa; Oladele, Omolade (Veterinaria Italiana, 2022)
This study investigated the occurrence of Escherichia coli O157:H7 and Salmonella spp. and their antimicrobial susceptibility from ducks and indigenous chickens in major live-bird markets at Ibadan, Oyo State, Nigeria. Thirty-one cloaca samples were each collected from both ducks and indigenous chickens in three different sample locations for a total of 186 cloacae swab samples. Isolation of Escherichia coli (E. coli) was done using MacConkey agar and Sorbitol MacConkey agar selective for E. coli O157:H7, while serological latex agglutination test kit was used to confirm isolates. Rappaport Vassiliadis and Xylose Lysine Deoxycholate agar were used for Salmonella spp. Antibiotic susceptibility was determined using the disc diffusion method and interpreted using the CLSI 2020 standards. Data were analyzed using descriptive statistics and Fisher’s exact test (p ≤ 0.05). Escherichia coli O157:H7 was confirmed in 31 samples (16.7%). E. coli isolates showed high resistance (90.3-93.5%) to cefuroxime, cefixime, ceftazidime, and amoxicillin, while they were highly susceptible to ofloxacin (96.8%) and gentamycin (80.7%). Salmonella was confirmed in 24 samples (12.9%). Salmonella showed 100% resistance to cefuroxime, cefixime ceftazidime, and amoxicillin, but was highly susceptible to gentamycin (91.7%) and nitrofurantoin (66.7%). No statistically significant association (p<0.05) was observed between the occurrence of E. coli O157 and Salmonella within the three live-bird markets. This study reveals that E. coli and Salmonella spp. occur in ducks and indigenous chickens from major live bird markets in Ibadan, Oyo state with antimicrobial susceptibility. Findings from this study underscores the need for further studies on these pathogenic organisms from ducks in Nigeria because there is paucity of data on this species of poultry that may serve as reservoir for these zoonotic organisms.